(untitled) (Scientific journal of the Fergana State University, 2023)
This article theoretically explores approaches to the content and essence of small business and private entrepreneurship in the context of the development of economic relations. At the same time, the main factors influencing the development of small businesses and private entrepreneurship and their specialization are studied.